Efektivitas Kegiatan Pembiasaan Pagi Dalam Menguatkan Hafalan Siswa - Merliana Merliana; Aisyah Putri Dea Palupi (LP3M IAI Al Urwatul Wutsqo Jombang, 2025)
This study aims to analyze the effectiveness of morning habituation activities in strengthening the memorization of the Qur'an of second-grade students at SD Islam Bunayya, Pagar Alam City. The research method used is descriptive qualitative with a field research approach. The subjects of the study were 20 second-grade students selected using a purposive sampling technique. Data collection was carried out through participatory observation, semi-structured interviews with students, class teachers, and tahfidz teachers, and documentation. Data analysis used the Miles and Huberman model with data reduction, data presentation, and conclusion drawing techniques. Data validity testing was carried out by triangulation of sources, techniques, and member checks. The results of the study indicate that the morning habituation activities carried out every day at 07.00-07.15 WIB were not effective in strengthening students' memorization. This was due to the implementation duration being too short (15 minutes), the material being too dense and diverse, and the mismatch between the muraja'ah material (Surah Al-Ikhlas to An-Nas) and the memorization achievement of students who had already reached longer surahs such as Al-Mulk and Al-Bayyina. Supporting factors included the religious environment, active teacher involvement, and infrastructure availability. Inhibiting factors included low student discipline, time constraints, unpredictable weather, and lateness of teachers on duty. This study contributes to an evaluative perspective on the morning recitation program and suggests the need to adapt the material to students' memorization achievement levels